PENGARUH PENERAPAN PSAK 72 TERHADAP KEBIJAKAN DIVIDEN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL: STUDI KASUS PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ketut Tanti Kustina; Bagus Danadyaksa Wijaya (Accounting Profession Journal (APAJI), 2023)
The purpose of this study was to determine the effect of applying PSAK 72 on dividend policy with firm size as the control variable. Researchers use secondary data sources in the form of financial statements of infrastructure companies collected using a documentation approach. The sample in the study consisted of 13 infrastructure companies listed on the Indonesia Stock Exchange. Based on research findings, the application of PSAK 72 to infrastructure businesses listed on the IDX has no impact on dividend policy. These findings indicate that infrastructure businesses listed on the IDX continue to provide dividends even though the impact of long-term contract revenue is not reflected in the financial statements on company profitability. Kata kunci: PSAK 72, Kebijakan Dividen, Ukuran Perusahaan, Pengakuan Pendapatan